PENDAMPINGAN PEMBUATAN ECOBRICK SEBAGAI UPAYA MENGURANGI SAMPAH PLASTIK DI SDK WOLOWIO - Marindo, Alfionita Frederika; Pare, Prisko Yanuarius Djawaria; Kua, Maria Yuliana (Lembaga Dongan Dosen, 2025)
The aim of providing assistance in making ecobricks ia as an effort to reduce the plastic waste at SDK Wolowio which is scattered around the school environment. This activity involved class V students from SDK Wolowio and 5 teaching campus students from STKIP Citra Bakti. The method used is mentoring. The results that were obtained after carrying out the assistance activity in making ecobricks were that the problem of waste was handled well because with this assistance, each homeroom teacher also started collecting plastic waste to make ecobricks for seats in their respective lasses. It is important to continue carrying out this activity to continue to train students’ character who cares about the environment.